Congenital asymmetric crying facies: A case report with review of the literature (Indian Journal of Case Reports, 2020)
Asymmetric crying facies (ACF) in a newborn is a condition which occurs in one in 160 live births, with an estimated prevalence in 0.2–0.6% of infants and the left-sided predominance was determined in 80% of neonatal ACF cases. When ACF is associated with other anomalies, it is known as ACF syndrome. Congenital ACF in a newborn is a rare condition caused by unilateral hypoplasia or agenesis of the depressor anguli oris muscle resulting in an ACF in the neonatal period. ACF is often confused with facial nerve compression of the fetus in the uterus or facial nerve palsy secondary to trauma. The present review is having a baseline single case study of ACF due to the left-sided congenital hypoplasia of depressor angularis oris muscle with no other anomalies. The differential diagnosis and complete physical examination are essential to rule out other associated anomalies in ACF cases.